Making social science matter : - Flyvbjerg, Bent (Cambridge University Press, 2001)
Making Social Science Matter presents an exciting new approach to social science, including theoretical argument, methodological guidelines, and examples of practical application. Why has social science failed in attempts to emulate natural science and produce normal theory? Bent Flyvbjerg argues that the strength of social science is in its rich, reflexive analysis of values and power, essential to the social and economic development of any society. Richly informed, powerfully argued, and clearly written, this book provides essential reading for all those in the social and behavioral sciences